The yield of nasopharyngeal bacteria from culture compared to polymerase chain reaction in South African children with lower respiratory tract infection - Pillay, Vashini (Department of Paediatrics and Child Health, 2023)
Background Lower respiratory tract infection (LRTI) is a major cause of morbidity and mortality in children under 5 years of age. Bacterial pathogens contribute significantly to this process. Culture of respiratory tract specimens is labour-intensive and slow. Polymerase chain reaction (PCR) is comparatively, a rapid, sensitive method of detecting low levels of nucleic acid for clinically relevant bacteria. This study compares the yield of bacteria obtained from culture and the FTDResp33 multiplex PCR of nasopharyngeal swabs (NPs) during LRTI episodes in children, in the Drakenstein Child Health Study. Methods At each episode of LRTI, 2 NPs were obtained, one for culture and one for PCR testing. Bacterial yields and concordance for the 5 commonest bacteria were compared using frequencies and proportions. Results From 13th August 2012 to 23rd November 2020, there were 859 episodes of LRTI in 434 children [median age 9.2 (IQR 3.8; 18.9) months; 0.2% HIV-infected]. S. pneumoniae, S. aureus, M. catarrhalis, H. influenzae and K. pneumoniae were the predominant bacteria detected by either method. Concordance between culture and PCR for S. pneumoniae, S. aureus, and K. pneumoniae was 84.9%, 89.7% and 86.3% respectively. Culture and PCR for H. influenzae had a concordance of 76.9%. The greatest discordance between culture and PCR was for the detection of M. catarrhalis (34.4%). Median bacterial loads on PCR for all 5 organisms were significantly associated with semi-quantitative culture results (p<0.001 for each). Adjusting for age and hospitalization, children on antibiotics at the time of sampling, had a reduced chance of having a positive culture (OR 0.1; 95% CI 0.1-0.4), and a reduction in PCR yield (OR 0.8; 95% CI 0.4-1.6). Conclusion: Significant concordance existed between PCR and culture for 4 of the 5 common bacteria, affirming PCR as a comparable method of testing to culture.